Pengembangan Buku Big Book “Miki Si Gajah Kecil” Sebagai Media Pengenalan Literasi Lingkungan - Indri Wijayani, Ida Ayu; Gede Anadhi, I Made; Komang Sindu Putra, Ida Bagus (UIR PRESS, 2023)
Environmental literacy is important for early childhood development as a cognitive experience of the natural environment. However, the introduction of environmental literacy in urban schools requires environmental literacy learning media. The purpose of the study was to develop an environmental literacy big book with the theme